Genetic variants in the VEGF pathway as prognostic factors in stages II and III colon cancer. Issue 4 (July 2018) - Riera, Pau; Virgili, Anna; Salazar, Juliana; Sebio, Ana; Tobeña, María; Sullivan, Ivana; Páez, David
Abstract The role of vascular endothelial growth factor (VEGF) gene polymorphisms in the prognosis of colon cancer prognosis remains unclear. We evaluated the influence of 28 single-nucleotide polymorphisms in 12 genes in the VEGF pathway on the prognosis of 347 patients with stage II–III colon cancer. We found that rs9513070 (VEGFR1 ) and rs1137282 (KRAS ) were associated with overall survival in stage II colon cancer patients (p = 0.025 andp = 0.001, respectively). When primary tumor location was considered, rs9513070 was also associated with relapse-free and overall survival (p = 0.033 andp = 0.031, respectively) in left colon cancer patients. Additionally, rs35251833 in theITGAV gene correlated with relapse-free survival (p = 0.032). This study provides evidence that germline polymorphisms inVEGFR1, KRAS andITGAV genes are associated with prognosis in stages II–III colon cancer patients. As stage and tumor location are correlated with prognosis, future genetic studies should stratify colon cancer patients according to these parameters.